International meeting on applied sciences and engineering (2018)
The goal aim objective of the 4th International Meeting on Applied Sciences and Engineering (EISI), is to promote a space for the exchange of knowledge between the academy and the industrial sector of the department of Norte de Santander, Colombia. The assistance of scientific experts in science, engineering, technological development, and innovation allowed generating knowledge and solutions that impacted the socio-economic development of the region and the country.